Improvement of citral antimicrobial activity by incorporation into nanostructured lipid carriers: A potential application in food stuffs as a natural preservative - Manijeh Mokarizadeh; Hossein Samadi Kafil; Saeed Ghanbarzadeh; Ainaz Alizadeh; Hamed Hamishehkar (Wolters Kluwer Medknow Publications, 2017)
At the present time, utilization of essential oils in food preservation to prevent bacterial and fungal growth and improve shelf life and safety of the food products has notably gained increased interest. The aim of the present study was to improve the antimicrobial efficacy of citral as a natural preservative using nanostructured lipid carriers (NLCs). Formulations of NLCs were characterized using particle size analysis and scanning electron microscopy methods. Possible citral-carrier interaction and citral encapsulation efficiency percent (EE%) were assessed by Fourier transform infrared (FTIR) spectroscopy and gas chromatography techniques, respectively. Antimicrobial activity, minimum inhibitory concentration (MIC), and minimum bactericidal concentration (MBC) of citral-loaded NLCs were evaluated and compared with the conventional citral emulsion against various gram-positive bacteria (Staphylococcus aureus, Bacillus cereus), gram-negative bacteria (Escherichia coli), and fungi (Candida albicans). Citral-loaded NLCs were spherically shaped nanosized (74.8 nm) particles with narrow size distribution, high EE% (99.84%), and appropriate physical stability during 90 days of storage period. FTIR spectra indicated the interaction between citral and formulation ingredients, which justified the obtained high EE% value. The MIC and MBC values of citral-loaded NLCs were lower than those of citral emulsion for all microorganisms. NLCs formulation showed remarkable capability of encapsulating essential oil and increasing antimicrobial properties to offer effective preservation in food industry.